City 5.0: Citizen involvement in the design of future cities - Jörg Becker; Friedrich Chasin; Michael Rosemann; Daniel Beverungen; Jennifer Priefer; Jan vom Brocke; Martin Matzner; Adela del Rio Ortega; Manuel Resinas; Flavia Santoro; Minseok Song; Kangah Park; et al. (Electronic Markets, 2023)
A citizen-centric view is key to channeling technological affordances into the development of future cities in which improvements are made with the quality of citizens' life in mind. This paper proposes City 5.0 as a new citizen-centric design paradigm for future cities, in which cities can be seen as markets connecting service providers with citizens as consumers. City 5.0 is dedicated to eliminating restrictions that citizens face when utilizing city services. Our design paradigm focuses on smart consumption and extends the technology-centric concept of smart city with a stronger view on citizens' roadblocks to service usage. Through a series of design workshops, we conceptualized the City 5.0 paradigm and formalized it in a semi-formal model. The applicability of the model is demonstrated using the case of a telemedical service offered by a Spanish public healthcare service provider. The usefulness of the model is validated by qualitative interviews with public organizations involved in the development of technology-based city solutions. Our contribution lies in the advancement of citizen-centric analysis and the development of city solutions for both academic and professional communities.
Keywords: O18; 620; Citizen involvement; Smart city; City 5.0; Restrictions; Future cities